La idealización del mercado - Miguel Catalán (Amnis)
This article studies from a critical perspective the phenomenon of the idealization of the economic concept of « Market ». The ideological process of the idealization of the Market has been carried out both by the classic liberalism of the eighteenth and nineteenth centuries and by the neoliberalism emerged in the 1980s in the twentieth century in the United States and the United Kingdom. By idealizing the economic functions of the market, the ideological elements of liberalism and neoliberalism have enthroned the blind forces of supply and demand as judges of human activity, not only from the economic point of view, but also moral and religious. This article exposes the fallacies, sophisms and euphemisms associated with this phenomenon that permeates the current socio-political reality.